Transcriptomes reveal microRNAs and mRNAs in different photoperiods influencing cashmere growth in goat. - Bin Liu; Ruoyang Zhao; Tiecheng Wu; Yuejun Ma; Yulin Gao; Yahan Wu; Bayasihuliang Hao; Jun Yin; Yurong Li (PLoS ONE, 2023)
Cashmere goat has a typical characteristic in seasonal growth of cashmere. Studies have shown that one of the main factors affecting the cyclical growth of the cashmere is the photoperiod, however, its molecular mechanism remains unclear. Inner Mongolia Arbas cashmere goat was used to reveal the mRNA-microRNA regulatory mechanisms of cashmere growth in different photoperiod. Skin samples from cashmere goats under light control (short photoperiod) and normal conditions (long photoperiod) were collected. Sequencing was performed after RNA extraction. The differentially expressed miRNA and mRNA expression profiles were successfully constructed. We found 56 significantly differentially expressed known mRNAs (P<0.01) and 14 microRNAs (P<0.05). The association analysis of the microRNAs and mRNAs showed that two differentially expressed miRNAs might be targeted by six differentially expressed genes. Targeting relationships of these genes and miRNAs are revealed and verified. In all, the light control technology provides a new way to promote cashmere growth. Our results provide some references in the cashmere growth and development.